Tumour discrimination using ultra-wideband (UWB) : early time tumour response - Ong, Ya Wen. (2011)
This report investigates the feasibility of a frequency-domain technique for classifying breast tumours into benign or malignant using only the early-time part of the UWB tumour responses. It reports findings and evaluates the accuracy of the technique by studying how the UWB early-time breast tumour backscatter responses are affected by the morphology of the tumour. The backscatter responses are then processed and classified using appropriate neural networks.